Implantable Brain Chips? Time for Debate - Maguire, G. Q. (The Hastings Center report, 1999)
We have long used mechanical devices to compensate for physical disability. Soon, however, it may be possible to augment mental capacity—to add memory or upgrade processing power. We should ponder the enormous moral implications of the machine-assisted mind now, before it is accomplished.